POPULATION DOCUMENTATION OF PELUNG CHICKENS IN FIVE SUB-DISTRICTS IN BANDUNG REGENCY - Budiarti, Yenti; Asmara, Indrawati Yudha; Garnida, Dani (Jurnal Produksi Ternak Terapan, 2023)
Pelung chicken is animal-genetic-resources which has a relatively larger physical appearance compared to other local chickens and has a long, melodious and rhythmic sound. Bandung Regency that has a fairly high population of Pelung chickens, but the number and structure of the population have not been documented. This research aims to determine the number and structure of the population, effective population size and inbreeding rate of Pelung chickens. The data collection technique was carried out by means of a survey, namely direct interviews with respondents in sub-districts including Ciparay, Kutawaringin, Katapang, Cicalengka and Cikancung. The variables observed in this research were male and female Pelung chickens grouped based on age, effective population size and inbreeding rate. The population data was then analyzed by quantitative descriptive method. The results showed that total population of Pelung chickens was 1,133 birds. The effective population size of Pelung chickens is 397 birds. The population structure of male Pelung 0-3 months was 228 birds, >3-6 months was 169 birds and >6 months was 201 birds, then for female Pelung chickens 0-3 months was 219 birds, >3-6 months was 119 birds and >6 months was 197 birds.  The inbreeding rate of Pelung chickens is 0.13%.